Measurement of pubic symphysis width in different birthing positions using ultrasound. (2nd December 2020) - Zhang, Shufei; Dumas, Geneviève; Hemmerich, Andrea
Abstract: Studies have shown that some vertical birthing positions, such as squatting and standing, may influence labour and childbirth. However, a rigorous biomechanical understanding of how different positions affect a woman's pelvis during labour is currently lacking. It was hypothesized that the position of pubic bones is affected in different positions, and thus the pubic symphysis width changes. Therefore, we measured pubic symphysis width on eleven women in their seventh to ninth months of pregnancy in different positions through three-dimensional (3D) reconstruction of pubic symphysis ultrasound images. Positions studies included those used in clinics like supine and lithotomy positions, in addition to squatting and standing, which are recommended by midwives. The results showed that the average superior and inferior pubic symphysis widths in lithotomy, squatting and standing positions were approximately 1 mm larger than those in the supine position. However, no significant difference between lithotomy, squatting and standing positions was found. The results were consistent with those of two comparable studies. A significant difference was only found between standing and squatting, standing and lithotomy in the rotation angle about the medio-lateral axis. The results suggest that positions with thigh hyperflexion and gravity effect make a difference in pubic symphysis width and might have a positive effect in childbirth. However, due to the small sample size, no definite conclusion can be drawn.